The Neural Correlates of Probabilistic Classification Learning in Obsessive-Compulsive Disorder: A Pilot Study - Hansmeier, Jana; Exner, Cornelia; Zetsche, Ulrike; Jansen, Andreas (Frontiers in Psychiatry, 2018)
Individuals suffering from obsessive-compulsive disorder (OCD) have been found to show deficits in implicitly learning probabilistic associations between events. Neuroimaging studies have associated these implicit learning deficits in OCD with aberrant activation of the striatal system. Recent behavioral studies have highlighted that probabilistic classification learning (PCL) deficits in OCD only occur in a disorder-specific context, while PCL remains intact in a neutral context. The neural correlates of implicit learning in an OCD-specific context, however, have not yet been investigated. Using functional magnetic resonance imaging (fMRI) during a neutral (prediction of weather) and an OCD-specific variant (prediction of a virus epidemic) of a probabilistic classification learning (PCL) paradigm, we assessed brain activity associated with implicit learning processes in ten participants with OCD and ten matched healthy controls. Regions of interest (ROIs) were the striatum and the medial temporal lobe. ROI analyses revealed significantly higher activity in the bilateral putamen and the left hippocampus of OCD participants as compared to healthy controls during both PCL tasks. These group differences could partly be subsumed under a group x task interaction effect with OCD participants showing significantly higher activity than controls in the left putamen and the left hippocampus in the OCD-specific task variant only. These results suggest a compensation of aberrant striatal activity by an augmented engagement of the explicit memory system particularly in a disorder-relevant context in OCD.